Redes de interação trófica de peixes em riachos expostos a diferentes pressões ambientais - Gambarotto, Bruno Luiz (2017)
Given the scenario of degradation of aquatic ecosystems - particularly those of lower order and more susceptible to stressors, such as streams - especially due to processes associated with urbanization and agriculture, the present study aims to compare the responses of the assemblies of fish from three basins exposed to different pressures arising from the use and occupation of the soil (urban, periurban and rural), specifically in relation to: (i) trophic structure; (ii) structure of the trophic networks (connectivity, link density, nestedness, modularity) and robustness; (iii) patterns of occupation of the ecomorphological space; and (iv) relationships between the parameters listed above and the landscape structure. The working hypothesis holds that the trophic networks of urban and rural streams respond differently to the impacts they are exposed to. The fish were collected with manual and electric fishing quarterly in the year 2013, in nine sampling points belonging to three basins: Ribeirão Cambé (essentially urban), Ribeirão Cafezal (inserted in a periurban context) and Ribeirão Taquara (essentially rural). A total of 815 individuals were analyzed, distributed among 19 species. From these species, 37 morphological characters were estimated, transformed into 22 ecomorphological indexes, for later calculation of the degree of packing of the ecomorphological space of the assemblies, through the metrics: distance to the nearest neighbor, mean distance to the centroid, and standard deviation from the distance to the nearest neighbor. Subsequently, the food items present in the gastrointestinal tract of the individuals were identified and the following topological properties of the networks (connectivity, bond density, nesting, modularity) and robustness were calculated. A total of 46 food items were identified, with P2 Taquara the richest, and P3 Cambé the least rich. The urban streams showed a trend of simplification and impoverishment. The rural points presented a tendency of greater nesting and robustness, suggesting greater complexity and stability, in comparison to the urban ones. Also in the rural streams it was possible to detect greater ecomorphological proximity between the species of the assembly, suggesting a tendency of specialization, unlike the urban ones, where the species were more distant. Thus, it can be concluded that the networks of trophic interaction, associated to the analyzes of occupation of the ecomorphological space, have proved to be interesting tools for the environmental analysis in streams, presenting results that suggest that the urban impacts tend to be more severe for the assemblies than rural ones.